Venous Hemorrhagic Infarct Leading to Delayed Brain Abscess Formation: A Case Report - Anshu Warade; Alay V. Khandhar; Charulata Sankhla; Ketan I. Desai (Indian Journal of Neurosurgery)
Venous sinus thrombosis is a common neurovascular problem with multifactorial etiology, infection being one of the common causes. Cerebral abscess causing thrombophlebitis and venous sinus occlusion is a known entity. In contrast, venous hemorrhagic infarct leading to abscess formation is extremely uncommon. We report a rare case of such delayed abscess formation in a venous hemorrhagic infarct secondary to superior sagittal sinus occlusion.